Identification of serologic markers for school-aged children with congenital rubella syndrome - Hyde, Terri B; Sato, Helena Keico; Hao, Li Juan; Flannery, Brendan; Zheng, Qi; Wannemuehler, Kathleen; Ciccone, Flavia Helena; Weckx, Lily Yin; Sáfadi, Marco Aurelio; Moraes, Eliane de Oliveira; Pinhata, Marisa Mussi; Olbrich Neto, Jaime [UNESP]; et al. (Oxford University Press (OUP), 2014)
Background: Congenital rubella syndrome (CRS) case identification is challenging in older children since laboratory markers of congenital rubella infection do not persist beyond age 12 months. Methods: We enrolled children with CRS born between 1998 and 2003 and compared their immune responses to rubella virus with their mothers’ or a group of similar-aged, non-CRS children. Demographic data and sera were collected. Sera were tested for anti-rubella immunoglobulin G (IgG), IgG avidity, and IgG response to the three viral structural proteins (E1, E2, and C) reflected by immunoblot fluorescent signals. Results: We enrolled 32 children with CRS, 31 mothers, and 62 non-CRS children. Immunoblot signal strength to C and C signal/rubella-specific IgG ratio concentrations, were higher (p<0.029) and, E1 signal/rubella-specific IgG ratio concentrations were lower in CRS children (p=0.001) than their mothers. Compared with non-CRS children, CRS children had more rubella-specific IgG (p<0.001), C signal (p<0.001) and E2 signal (p=<0.001). Two classification rules for CRS children versus non-CRS children gave 100% specificity with greater than 65% sensitivity Conclusions: This study was the first to establish classification rules for identifying CRS in schoolaged children using laboratory biomarkers. These biomarkers should allow improved burden of disease estimates and monitoring of CRS control programs.